Pt-anchored-zirconium phosphate nanoplates as high-durable carbon-free oxygen reduction reaction electrocatalyst for PEM fuel cell applications - Kumar, Sachin; Yoyakki, Athira; Pandikassala, Ajmal; Soni, Roby; Kurungot, Sreekumar (Advanced Sustainable Systems, 2023)
Commercially available platinum-supported carbon (Pt/C) catalysts are the most widely used oxygen reduction reaction (ORR) electrocatalysts in polymer electrolyte membrane fuel cells (PEMFCs). However, inadequate active triple-phase boundary formation and carbon oxidation in Pt/C during PEMFC operation shorten its lifetime and efficiency. In this direction, a new class of carbon-free electrocatalysts for ORR is prepared by dispersing Pt nanoparticles on ZrP (Zirconium phosphates) nanoplates. In one case (ZrP@Pt), the Pt nanoparticles are found to be closely distributed and completely covering the ZrP nanoplates, whereas in the second case (Pt/ZrP), the Pt nanoparticles selectively restrict dispersion along the edges of the support. ZrP as the support displays an intrinsic proton conductivity of approximate to 0.5 x 10(-4) S cm(-1) at 70 degrees C, with an activation energy (E-a) of 0.19 eV. Pt/ZrP shows better durability after 3000 start-stop cycles. The mass activity of Pt/ZrP is increased by 4.6 times compared to Pt/C, which exhibits a loss in mass activity by 1.37 times. The single-cell level validation of ZrP@Pt, Pt/ZrP, and Pt/C as the electrocatalysts in PEMFC at an operating potential of 0.60 V shows the achievable current densities of 0.600, 0.890, and 0.890 A cm(-2).
Keywords: carbon-free electrocatalysts; fuel cells; oxygen reduction reaction; zirconium phosphate

Aluminium, nitrogen-dual-doped reduced graphene oxide Co-existing with cobalt-encapsulated graphitic carbon nanotube as an activity modulated electrocatalyst for oxygen electrocatalyst for oxygen electrochemistry applications - Kharabe, Geeta Pandurang; Barik, Sidharth; Veeranmaril, Sudheesh Kumar; Nair, Aathira; Illathvalappil, Rajith; Yoyakki, Athira; Joshi, Kavita; Vinod, Chathakudath Prabhakaran; Kurungot, Sreekumar (Small, 2024)
There is a rising need to create high-performing, affordable electrocatalysts in the new field of oxygen electrochemistry. Here, a cost-effective, activity-modulated electrocatalyst with the capacity to trigger both the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) in an alkaline environment is presented. The catalyst (Al, Co/N-rGCNT) is made up of aluminium, nitrogen-dual-doped reduced graphene oxide sheets co-existing with cobalt-encapsulated carbon nanotube units. Based on X-ray Absorption Spectroscopy (XAS) studies, it is established that the superior reaction kinetics in Al, Co/N-rGCNT over their bulk counterparts can be attributed to their electronic regulation. The Al, Co/N-rGCNT performs as a versatile bifunctional electrocatalyst for zinc-air battery (ZAB), delivering an open circuit potential approximate to 1.35 V and peak power density of 106.3 mW cm-2, which are comparable to the system based on Pt/C. The Al, Co/N-rGCNT-based system showed a specific capacity of 737 mAh gZn-1 compared to 696 mAh gZn-1 delivered by the system based on Pt/C. The DFT calculations indicate that the adsorption of Co in the presence of Al doping in NGr improves the electronic properties favoring ORR. Thus, the Al, Co/N-rGCNT-based rechargeable ZAB (RZAB) emerges as a highly viable and affordable option for the development of RZAB for practical applications. This manuscript reports the development of a new bifunctional catalyst that exhibits high activity and stability under practical operating conditions. The catalyst (Al, Co/N-rGCNT) is made up of aluminium, nitrogen-dual-doped reduced graphene oxide sheets co-existing with the in situ formed cobalt-encapsulated CNT units is synthesized by a scalable pyrolysis method in an inert Ar atmosphere. The developed electrocatalyst achieved enhanced the oxygen reduction reaction (ORR) and the oxygen evolution reaction OER activity as a result of the favorable synergistic modulations and the system can serve as a process-friendly air-electrode for rechargeable zinc-air battery (RZAB). image
Keywords: Al; Bifunctional catalyst; DFT study; encapsulated structure; N-dual doping; Oxygen Evolution Reaction; oxygen reduction reaction; rechargeable zinc-air battery; X-ray absorption spectroscopy

Breaking the Pt electron symmetry and OH spillover towards ptir active center for performance modulation in direct ammonia fuel cell - Barik, Sidharth; Kharabe, Geeta Pandurang; Samal, Pragnya Paramita; Urkude, Rajashri R.; Kumar, Sachin; Yoyakki, Athira; Vinod, C. P.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Small, 2024)
The growing interest in low-temperature direct ammonia fuel cells (DAFCs) arises from the utilization of a carbon-neutral ammonia source; however, DAFCs encounter significant electrode overpotentials due to the substantial energy barrier of the *NH2 to *NH dehydrogenation, compounded by the facile deactivation by *N on the Pt surface. In this work, a unique catalyst, Pt4Ir@AlOOH/NGr i.e., Pt4Ir/ANGr, is introduced composed of PtIr alloy nanoparticles controllably decorated on the pseudo-boehmite phase of AlOOH-supported nitrogen-doped reduced graphene (AlOOH/NGr) composite, synthesized via the polyol reduction method. The detailed studies on the structural and electronic properties of the catalyst by XAS and VB-XPS reveal the possible electronic modulations. The optimized Pt4Ir/ANGr composition exhibits a significantly improved onset potential and mass activity for AOR. The DFT study confirms the OHad species spillover by AlOOH and Pt4Ir (100) facilitates the conversion of the *NH2 to *NH with minimal energy barriers. Finally, testing of DAFC at the system level using a membrane electrode assembly (MEA) with Pt4Ir/ANGr as the anode catalyst, demonstrating the suitability of the catalyst for its practical applications. This study thus uncovers the potential of the Pt4Ir catalyst in synergy with ANGr, largely addressing the challenges in hydrogen transportation, storage, and safety within DAFCs. In this article, a versatile catalyst, Pt4Ir/ANGr, is introduced composed of PtIr alloy nanoparticles decorated on AlOOH/NGr composite. The AlOOH provides an -OH-rich surface conducive to the facile adsorption and decoration of the PtIr alloy nanoparticles and OHad species spillover from AlOOH to the Pt4Ir active center during AOR, further validating the higher experimental activity obtained in Pt4Ir/ANGr. image
Keywords: ammonia oxidation reaction (AOR); d-band center; density functional theory (DFT) study; direct ammonia fuel cells; hydroxyl spillover effect; XAS analysis

Surface-anchored PtNi alloy network over SiO2 (PtNi/SiO2): a versatile carbon-free cathode for proton exchange membrane fuel cells (PEMFCs) - Kumar, Sachin; Yoyakki, Athira; Kurungot, Sreekumar (ACS Applied Engineering Materials, 2024)
The large-scale commercialization of the PEMFCs is hindered due to the high cost of the Pt-based electrocatalysts (Pt/C) and the low durability associated with the oxidation of the carbon support in Pt/C. Many Pt-based carbon-free electrocatalysts have been explored, exhibiting excellent stability and activity, but the performance is further expected to be improved by developing suitable Pt alloy catalysts based on the carbon-free supports. To explore this possibility, we have developed a PtNi/SiO2 alloy system, which acts as a carbon-free electrocatalyst exhibiting enhanced activity for the oxygen reduction reaction (ORR). A half-cell study of PtNi/SiO2 (45 wt%) shows ∼4.3 times higher ORR activity compared to the state-of-the-art Pt/C (40%). The uniform distribution of the PtNi nanoparticles over SiO2 is the crucial feature of the catalyst. PtNi/SiO2 shows better durability even after 5000 cycles compared to the state-of-the-art Pt/C. The catalyst shows a negative shift in the half-wave potential (E1/2) by only 5 mV, which is lower than that of the 11 mV drop incurred by Pt/C. Considering this high activity of the PtNi/SiO2 catalyst for the ORR, we tried to explore the possibility of demonstrating a single-cell PEMFC in the MEA by pairing the catalyst as the cathode along with the Pt/C as the anode. This paired configuration of the single cell is found to be providing promising performance by delivering a current density of 960 mA/cm2 at 0.60 V and a maximum power density of 835 mW/cm2. Thus, this study outlines the possibility of developing potential alloy combinations of Pt on carbon-free substrates and then deploying them as electrodes for PEMFC applications. In the context of mitigating the carbon corrosion-related issues without compromising the intrinsic activities of the catalysts, the development of suitable alloy combinations on various carbon-free substrates is of significant technological advantages. The formation of the alloy phase along with the fine and uniform distribution of the alloy nanoparticles on the SiO2 substrate, followed by its successful deployment as the cathode of a single cell, points toward the scope of exploring material developments in this direction.

Pt-based 3D electrocatalyst with process-friendly features for PEMFCs possessing fast activation and improved mass-transfer properties - Pandikassala, Ajmal; Nadumattuvayil, Varsha; Singh, Mayank U.; Jadhav, Swapnil D.; Yoyakki, Athira; Kurungot, Sreekumar (Advanced Sustainable Systems, 2025)
Polymer-electrolyte-membrane fuel cells (PEMFCs) face the challenges like slow oxygen reduction reaction (ORR) kinetics and limited mass transport at high current densities, which affects their performance. The efficient water removal from the cathode is essential to improve oxygen diffusion. Addressing this, a catalyst is presented with platinum (Pt) nanoparticles distributed within a 3D carbon network (Pt/3DPDC) derived from the polydopamine-coated melamine foam. This unique architecture enhances Pt utilization and water management due to its high porosity and ample free spaces, providing a process-friendly feature for the electrode under PEMFC conditions. The pores and accessible texture of the 3D polydopamine derived carbon (3DPDC) framework facilitate ionomer uptake during the electrode fabrication, extending the active triple-phase boundary and improving the membrane electrode assembly (MEA) performance. The high porosity of Pt/3DPDC is mitigated by adding a small amount of commercial fuel cell catalayst (Pt/C), which maintains the effective catalyst number density per unit area by utilizing the excess porosity of the 3DPDC framework. This controlled interplay of the unique catalyst structure and spatially confined distribution of Pt/C within the Pt/3DPDC framework offers fast activation, reduced electrode flooding, and improved current densities across the operating potential window. This carefully engineered catalyst, designed through bottom-up strategies, is a promising electrocatalyst for practical PEMFC applications.
Keywords: Oxygen Evolution Reaction; oxygen reduction reaction; rechargeable flexible zinc-air battery

A Pt-Based Carbon-Free Cathode with Embedded Oxygen Nanoreservoirs: A Promising Approach for Oxygen Buffering to Aid Oxygen Reduction Reactions of PEMFCs - Yoyakki, Athira; Kumar, Sachin; Pandikassala, Ajmal; Jadhav, Swapnil D.; Vinod, C. P.; Kurungot, Sreekumar (ACS Catalysis, 2025)
For practical applications of proton exchange membrane fuel cells (PEMFCs), the system needs to be operated by employing air in the cathode instead of pure oxygen (O2). This makes it necessary to develop innovative electrode engineering solutions so that the system can function well even in oxygen-lean environments under the realistic working conditions of PEMFCs. Taking this into account, we introduce Pt/SiO2@CeO2-30%, an engineered electrocatalyst with potentially generated oxygen vacancies (Ov), which can immensely contribute toward the enhancement in the O2 availability in oxygen-lean conditions like the air feed conditions, allowing an effective control of the overpotential related to the oxygen reduction reactions (ORRs) at the electrode level. The meticulously crafted Pt-CeO2 interface serves as one of the appreciable structural attributes of the present catalyst, facilitating oxygen spillover toward the Pt environment, aided by the creation of the immense Ov along the nano CeO2 phase of the catalyst. In addition to the benefit of addressing the oxygen-lean conditions and overcoming the limitations of the state-of-the-art catalysts, usage of a noncarbonaceous support like SiO2 to house the Pt and CeO2 nanoparticles has been anticipated to lessen the corrosion problems, a major drawback associated with the carbon-based ORR catalysts. Apart from this, a significant contribution of SiO2 to the self-humidification of the ionomer interface plays a crucial role in enabling the MEA to work under low relative humidity conditions, which can be attributed to an additional benefit of the current composition of the catalyst. The catalyst demonstrated a promising ORR performance with a substantial improvement in H2-air feed circumstances and better corrosion resistance when tested with a membrane electrode assembly (MEA) in a single-cell configuration, illustrating the practical feasibility in a realistic system-level validation.
Keywords: carbon corrosion; carbon-free electrocatalyst; oxygen buffering; oxygen reductionreaction; oxygen spill over; protonexchange membrane fuel cell